Reliability and validity of an instrument to measure the socio-political dimension of the quality of life - García Lirios, Cruz (Consorcio de Universidades Mexicanas A.C., 2015)
The quality of life has been approached from socio-economic approaches that highlight the dimensions of well-being and ability as two axes prevailing theoretical and conceptual discussion. However, from a psychological view, this paper established the reliability and validity of an instrument that measured eight factors indicative of sociopolitical dimension of quality of life. For this purpose, we conducted a cross-sectional study with a probabilistic sample of 245 students. Therefore, life satis- faction (alpha = 0.72; 45% of the explained variance), expected capacity (alpha = 0.74; 37%), trust relationships (alpha = 0.79; 33%), perception justice (alpha = 0.74; 31%), expectations of opportunity (alpha = 0.78; 27%), environmental assessments (alpha = 0.75; 25%), context rules (alpha = 0.71; 23%) and perceived resources (alpha = 0.75; 21%) were established as indicative factors of sociopo- litical dimension of quality of life [KMO = 6.25; chi-square = 14.25 (23 gl) p = 0.000]. Regarding the state of knowledge that has weighed directly to the quality of life from the subjective well-being and economic capabilities, the findings of this study were discussed to explain a scenario of economic and social crisis to which governors and governed react asymmetrically.